Optimization of power management in PV-based smart grids using grid-support and grid-forming inverters - Amam Hossain Bagdadee; Ishtiak Al Mamoon; Deshinta Arrova Dewi; A. K. M. Muzahidul Islam; Li Zhang (PLoS ONE, 2026)
This paper addresses the synthesis and analysis of advanced control strategies in photovoltaic (PV) based smart grids with distributed generation, focusing on grid support and grid-forming inverters. The penetration level of renewable energy sources such as photovoltaic (PV) systems is on the rise, and maintaining grid reliability, smooth power management, and secure power-sharing has become difficult. It is anticipated that the control approaches are able to optimally allocate power among PV generation, energy storage systems and load without compromising on grid-tied stability in both on-grid and island modes of operation. These kinds of grid-support inverters can offer essential ancillary services as voltage and frequency regulation, which should be cost-effectively supported in a grid-connected operation. In isolated mode, however, the grid-forming inverters are in normal operation. The novel optimal power-sharing strategy developed in this paper can further achieve real-time coordination of distribution generation units’ power allocation, to reduce dependence on PV output variation. Results from the simulations, carried out using Simulink, demonstrate that these methods result in direct assistance in grid operation, loss reduction and system restoration. Based on the results, the proposed system has a superior ability in terms of power regulation, stability and quality control than conventional methods.